Stress : a Brief History. - Cooper, Cary L. (Blackwell brief histories of psychology., 2007)
Stress: A Brief History is a lively, accessible, and detailed examination of the origins of the field of stress research.:.; First concise, accessible, academically grounded book on the origins of the concept of stress.; Explores different theories and models of stress such as the psychosomatic approach, homeostasis, and general adaptation syndrome.; Discusses the work and intriguing contributions of key researchers in the field such as Walter Cannon, Hans Selye, Harold Wolff, and Richard Lazarus.; Explains the origins of key concepts in stress such as stressful life events, the coronary-prone.